Impact of the Great Postal Road on Infrastructure Development and Social Dynamics in Java under Herman Willem Daendels - Devit Eskan Putrama Tarigan; Bagas Ibnu Andira; Munajatun Nasih; Risky Dwi Ananda; Shella Ananda Putri; Rosmaida Sinaga (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The construction of Great Postal Road, known as the De Grote Postweg, played a transformative role in shaping infrastructure development and social dynamics in Java during the early 19th century. This study examines the historical context, motivations, and impacts of the 1,000 km road, stretching from Anyer to Panarukan, constructed under the administration of Governor-General Herman Willem Daendels. Employing the historical method, the research follows a four-step process: heuristics, verification, interpretation, and historiography, ensuring data accuracy and reliability. The findings reveal that the primary objectives of the road were to improve communication across Java and bolster defenses against British threats along the northern coast. Furthermore, the construction resulted in substantial changes to the island's infrastructure and brought profound socio-economic consequences to the local population. This article concludes that although the road primarily served colonial interests, its enduring legacy significantly influenced the socio-economic transformation of the regions it traversed.